HAGAR, O HORRÍVEL: A PERSPECTIVA FUNCIONALISTA DAS ADVERBIAIS FINAIS E TEMPORAIS NOS DIÁLOGOS DOS PERSONAGENS - Amaro, Natalia Crissaff (2020)
The subordinate clauses, adverbial and relative, in general matter, are treated by Ordinary Grammars (OGs) as cases of subordination and are explained from the idea of syntactic dependence. These OGs indicate to subordination as the opposite of coordinati